Stress-Strain Behaviour of Reparable Composite Panel with Step-Variable Thickness - Kondratiev, Andrii; Píštěk, Václav; Smovziuk, Lina; Shevtsova, Maryna; Fomina, Anna; Kučera, Pavel (Polymers, 2021)
There is an urgent problem of finding an economically viable method of maintenance and restoration of the bearing capacity of structures of various applications. Repair of structures with patches made of polymeric composite materials is one of the most promising repair technologies. However, an improper choice of parameters of the composite patch leads to unjustified increase in the structure mass and the cost of its further operation. These situations result from the lack of reliable methods for developing the repair process, which take into account the influence of the patch geometry and conditions for performance of repair works on the bearing capacity of the repaired structure. The mathematical model of the reparable composite shell-type panel taking into account inhomogeneity of transverse shear deformations at stepped variation of its thickness has been developed. In contrast to the classical theory of layered shells, the model allows simplifying a three-dimensional problem by setting of the displacement field on the layers' interfaces and their linear interpolation over thickness of the panel, as well as considering the transverse shear deformations resulting from the strength, temperature, or shrinkage loading. According to results, the maximum rise in stresses in the case of a notched panel occurs in the weakened layer, and it is from this layer the failure of the structure will start. In the event of the patch, the panel surface opposite the reinforcement is the most loaded (i.e., susceptible to failure) surface. To confirm the reliability of the developed model, we compared the analytical calculations with the results of experimental and numerical studies of the deformed state of a panel of step-variable thickness by the method of holographic interferometry and modelling by the finite element method. Displacement fields available from experiments correspond to the predicted theoretical results. The resulting maximum error does not exceed 7%. The data obtained during numerical modelling allowed us to conclude that the accuracy of theoretical calculations is sufficient for engineering practice. Results of the work can be used to solve the practical problems such as determination of stress-strain behaviour of a damaged structure or structure after repair, specification of the permissible delamination dimensions, and defining of parameters of the bonded repair process.
Keywords: patch; transverse shear; notch; anisotropic shell